Learning Achievement of Elementary School Students of Ichhawar Block of Madhya Pradesh A Trends Analysis - Pradhan, Nityananda; Garg, Ashwani Kumar (JOURNAL OF INDIAN EDUCATION, 2022)
This paper is based on the results of NCERT’s longitudinal study being conducted since 2017–18 Ichhawar block of Sehore district, Madhya Pradesh. The paper compiles data on the learning achievement of elementary school level students from three research reports of the same title ‘Implementing Interventions at the School Stage: Learning Levels of Elementary School Students in Ichhawar Block’, brought out by the Regional Institute of Education in the years 2017–18; 2018–19 and 2019–20. The levels of learning outcomes of 43,084 children (Classes III to VIII) of Ichhawar block, assessed through National Achievement Survey (NAS) tools developed by NCERT, are subjected to cluster-wise analysis of the trend of growth/change in learning levels of students in basic school subjects, as a result of various training-based interventions provided by NCERT during these years. The analysis revealed an overall incremental growth in the rate of learning achievement of both primary as well as upper primary school children in all the basic school subjects, viz., environmental studies, mathematics, science, social science and language, across 10 education clusters of the block. These results imply that further training of teachers need to be undertaken after identification of the training needs in different subjects as well as cross-cutting areas, keeping in view the philosophy of India’s National Education Policy 2020.